Lecture correspondence and literary drafts by Hanna Sheehy-Skeffington - Sheehy-Skeffington, Hanna, 1877-1946
Titles include 'The U.S.A. - Ten Years After', '"Kingfish", Louisiana's Dead Dictator', 'Ireland and America (Impressions of Sinn Féin in the United States)', and 'Books on Dublin and Dubliners'.
Keywords: Sinn Féin; Playscripts -- Ireland -- 20th century; Irish Americans; Ireland -- History -- 20th century; Ireland -- Foreign relations -- United States